2005
DOI: 10.1080/02699930441000184
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety, anxiety sensitivity, and attentional biases for pictorial and linguistic health‐threat cues

Abstract: The study investigated attentional biases for pictorial and linguistic health-threat stimuli in high and low health anxious individuals, who were selected from the upper and lower quartile ranges of a normal sample using a screening measure of health anxiety. Attentional bias was assessed using a visual probe task which presented health-threat and neutral pictures and words at two exposure durations, 500 ms and 1250 ms. The prediction that the high health anxious group would show a greater attentional bias for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 26 publications
5
79
1
Order By: Relevance
“…The results of dot-probe studies conducted with nonanxious individuals are less consistent. Studies with nonfacial stimuli mostly did not find a bias for threat stimuli (e.g., Mogg & Bradley, 2006;Lees et al, 2005). In contrast, some studies with facial stimuli found a bias toward threat (e.g., Tomaszczyk & Fernandes, 2014), some studies found a bias away from threat (e.g., Bradley et al, 1997) and yet other studies found no bias (e.g., Bradley et al, 1998).…”
Section: Types Of Stimulimentioning
confidence: 80%
See 2 more Smart Citations
“…The results of dot-probe studies conducted with nonanxious individuals are less consistent. Studies with nonfacial stimuli mostly did not find a bias for threat stimuli (e.g., Mogg & Bradley, 2006;Lees et al, 2005). In contrast, some studies with facial stimuli found a bias toward threat (e.g., Tomaszczyk & Fernandes, 2014), some studies found a bias away from threat (e.g., Bradley et al, 1997) and yet other studies found no bias (e.g., Bradley et al, 1998).…”
Section: Types Of Stimulimentioning
confidence: 80%
“…Longer stimulus presentation seems to affect performances of anxious individuals who shifted from vigilance to avoidance of threat with longer stimulus presentation. Yet, nonanxious individuals did not show different attentional biases (e.g., Ioannou et al, 2004;Lees et al, 2005). In addition, whether the dot-probe task applied probe detection or probe discrimination does not seem to significantly affect results Mogg & Bradley, 1999).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[9], [12]] or the dot-probe task [e.g. [13], [14]] to investigate preferred attention allocation towards illness-related stimuli in HA. The EST is assumed to depict the tendency for aversive stimuli to capture attention and slow down information processing due to an interference of their emotional connotation with the actual task demand [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on health anxiety have examined the cognitive processes in maintaining health anxiety [10]. A critical review of studies examining cognitive processes implicated in health anxiety [11] reported that health anxious individuals tend to negatively emotion as indicating an illness, a phenomenon known as amplification.…”
Section: Review Of the Literaturementioning
confidence: 99%